2010
DOI: 10.1108/07419051011095872
|View full text |Cite
|
Sign up to set email alerts
|

Training in the use of e‐resources in academic libraries: one university's approach

Abstract: PurposeThe purpose of this paper is to reflect on the experience of the Redeemer's University Library in Nigeria in its information literacy (IL) training programs.Design/methodology/approachThe paper provides a brief literature review of current trends in IL training and challenges. A description of methods of training, schedules, content of IL, successes, and shortcomings are detailed. Information and data for the paper were collected from records kept by the IL librarian. The experiences of the authors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…Unfortunately, some of the graduate students do not avail themselves to the training programs. The finding supports the work of Adeleke and Olorunsola (2010), who reported that a high percentage of students in Redeemer University in Nigeria had training regarding access and use of electronic resources.…”
Section: Research Question 3: What Level Of Training Is Provided By Tsupporting
confidence: 87%
“…Unfortunately, some of the graduate students do not avail themselves to the training programs. The finding supports the work of Adeleke and Olorunsola (2010), who reported that a high percentage of students in Redeemer University in Nigeria had training regarding access and use of electronic resources.…”
Section: Research Question 3: What Level Of Training Is Provided By Tsupporting
confidence: 87%
“…The lack of awareness might by as a result of the inability of the medical library to educate and train users on online information resources. This may be why Adeleke and Olorunsola (2010) stated that``it is one thing to make users aware of the e-resources available in the library, whereas it is another to train the users on how to access such electronic resources. It is the only way that academic libraries can help students learn and work in the digital Evidently, none of the students interviewed mentioned using medical databases like Medline, CINAHL and HINARI.…”
Section: Discussionmentioning
confidence: 99%
“…Writing on the training in the use of e-resources in academic at the Redeemer's University in Nigeria, Adeleke and Olorunsola (2010) reported that``as soon as the library started subscribing to e-resources, efforts were put in place to train users on how to access the resources, particularly databases under the AGORA and HINARI programs which are used by both faculty and students''. Lwehabura (2008a) in his study on skills and training needs for use of electronic information resources (EIRs) among students in four Tanzanian universities revealed that although students in Tanzanian universities have access to and use various EIRs both for academic and non-academic work, they still lack adequate knowledge and skills in some aspects, including searching and evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These approaches have been confirmed to yield good results in the library where they were used as reported by Adeleke and Olorunsola (2010).…”
Section: Information Literacy Approaches In Nigerian Librariesmentioning
confidence: 83%
“…However, personal experience of one of the researchers had shown that some libraries, particularly academic libraries, adopt and adapt the two IL approaches and found them to yield good results in the academic library where they were used (Adeleke and Olorunsola, 2010). The approaches are: ◊ group method designed for students on subject related database in the faculties of Natural sciences, Humanities, Social/Management sciences, and project writing students in their final classes; ◊ individual training approach in which staff and students voluntarily approach the e-resources librarian for training particularly in the area of online resources.…”
Section: Information Literacy Approaches In Nigerian Librariesmentioning
confidence: 99%